A Dramatic Fall: Critical Discourse Analysis of Boris Johnson’s Resignation Speech (Nusantara Science and Technology Proceedings, 2022)
This study aimed to dissect the image formed by Boris Johnson in his resignation speech as British Prime Minister. A qualitative descriptive method was used in this study with Critical Discourse Analysis by Norman Fairclough. Analysis at the micro level using transitivity suggested that Boris Johnson mostly used mental processes, especially in the process of desirability. The data found that there were 11 uses of modality such as 'should', 'will', and 'can'. This data mostly showed the probability that the former prime minister suggested when dealing with the future programs that would be conducted without his concern any longer. Among 73 data points of pronouns, the pronoun 'I' dominated the content of the speech, followed by the pronouns' we' and 'our', which had 12 data points each. The pronoun 'I' indicated the unmarked theme (subject/theme) in a declarative clause to only concern the former prime minister himself. Socially, situationally, and institutionally, it can be seen that Boris Johnson received pressure to step down from his position. Based on the discussion, it can be concluded that Boris Johnson wanted to build an image that he was a successful leader and still willing to contribute even after he was no longer in office. Further research could be carried out, especially in terms of research on the resignation speeches of world leaders.